Improving Students' Conceptual Understanding of SD Negeri 10 Tarung Tarung Utara in Islamic Education Learning Using Discussion Methods - Pebrina (DARUSSALAM: Scientific Journal of Islamic Education, 2024)
This study aims to improve student learning outcomes in Islamic religious education learning by using the discussion method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that the discussion method can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 49.71%, the first cycle 69.19% and in the second cycle it increased to 91.31%. Thus, the use of the discussion method can be used as an alternative to improve student learning outcomes in Islamic religious education learning.